2013
DOI: 10.3389/fpls.2013.00386
|View full text |Cite
|
Sign up to set email alerts
|

Diversification of the phaseoloid legumes: effects of climate change, range expansion and habit shift

Abstract: Understanding which factors have driven the evolutionary success of a group is a fundamental question in biology. Angiosperms are the most successful group in plants and have radiated and adapted to various habitats. Among angiosperms, legumes are a good example for such successful radiation and adaptation. We here investigated how the interplay of past climate changes, geographical expansion and habit shifts has promoted diversification of the phaseoloid legumes, one of the largest clades in the Leguminosae. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 58 publications
7
31
0
Order By: Relevance
“…C) support Shuteria as sister to Kennedia , a finding also discovered by Li et al. (), whereas ASTRAL (Fig. B) and the concatenated chloroplast loci (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…C) support Shuteria as sister to Kennedia , a finding also discovered by Li et al. (), whereas ASTRAL (Fig. B) and the concatenated chloroplast loci (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…Thus, our DNA sequence data support Apios as a monopyletic group. In addition, Apios diverges early in the phaseoloid group, which is consistent with the phylogenetic placement of Apios by previous studies (Kajita et al 2001;Wojciechowski et al 2004;Lavin et al 2005;Stefanovic et al 2009;Li et al 2013).…”
Section: Phylogeneticssupporting
confidence: 87%
“…Two areas of endemism were used on the basis of the distribution of the extant species: EAS and ENA. The outgroup was included in the S-DIVA analysis and was coded as EAS since a recent study of phaseoloid legumes has inferred EAS as the most likely ancestral area of the sister group to Apios (Li et al 2013). …”
Section: Biogeographic Analysesmentioning
confidence: 99%
“…Some studies have indicated that life history shifts are responsible for increased rates of diversification of many groups, such as Lupinus [ 55 ] and the phaseoloid legumes [ 61 ]. Our ancestral state reconstruction suggests that perennial life history is the ancestral state in Oryza , whereas annual life history has independently evolved at least four times (Fig.…”
Section: Discussionmentioning
confidence: 99%